Pengaruh Corporate Social Responsibility terhadap Kinerja Perusahaan Sektor Pertambangan Terdaftar di Bursa Efek Indonesia&Malaysia 2014-2018 - Irbahiya Aqsa Griselda; Werner Ria Murhadi; Mudji Utami (Program MM Universitas Surabaya, 2020)
The aims of this research is to analyze the effect of corporate social responsibility, leverage, firm size and firm size towards firm performance using return on assets and Tobin’s Q as a proxy in mining sector companies listed in Indonesian Stock Exchange and Malaysia Stock Exchange in the period 2014-2018. This research uses quantitative approach with two least square regression analysis model. This study uses sample of firms which are listed on mining in IDX and MYX on 2014-2018. The findings result of this research CSR have positive and significant effect towards firm performance in mining sector companies BEI on the period 2014-2018, while CSR insignificant effect towards firm performance in mining sector companies BEM on the period 2014-2018. Keywords: corporate social responsibility, financial performance, firm value